Neural Network Based Color Recognition for Bobbin Sorting Machine - Mu Zhang; Xueqian Ding; Xin Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Winding is a key process in the manufacturing process of textile industry. The normal and effective operation of winding process plays a very important role on the textiles’ quality and economic effects. At present, a large proportion of bobbins which collected from winder still have yarn left over. The bobbin recycling is severely limited and quick running of winder is seriously restricted, the invention of the the automatic bobbin sorting machine has solved this problem. The ability to distinguish bobbin which has yarn left over from the rest and the classification accuracy of color are the two important performance indicators for bobbin sorting machine. According to the development and application of the color recognition technology and the artificial intelligence method, this study proposes a novel color recognition method that based on BP neural networks. The result shows that the accuracy of color recognition reaches 98%. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2820